2015
DOI: 10.17116/jnevro201511510222-27
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of the efficacy of neuromidin and galantamine in Alzheimer’s disease

Abstract: The results suggest that the effectiveness of anticholinesterase treatment of Alzheimer's disease could be determined not only by the central but also peripheral cholinergic action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This drug was the subject of several studies published in Russian in this country, which have shown some therapy benefits for dementia patients [19][20][21][22]. The efficacy and safety of galantamine, which is frequently used in Russia, was also demonstrated [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…This drug was the subject of several studies published in Russian in this country, which have shown some therapy benefits for dementia patients [19][20][21][22]. The efficacy and safety of galantamine, which is frequently used in Russia, was also demonstrated [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…To create new homobivalent MTDLs within the present study, we used another anticholinesterase pharmacophore—the amiridine molecule. Amiridine is an anticholinesterase drug that has found use in Russia and some other countries in Eastern Europe as a therapeutic agent for AD and certain other neurological disorders [ 70 , 71 , 72 , 73 , 74 , 75 ]. Known to inhibit AChE and BChE, with more potency against the latter enzyme, amiridine also exhibits numerous other biological activities [ 76 , 77 ] that have been reviewed in our previous publication [ 78 ].…”
Section: Introductionmentioning
confidence: 99%